Ducting of incoherent scatter radar waves by field-aligned irregularities - Rietveld, Michael T; Senior, Andrew (Annales Geophysicae, 2020)
We provide an explanation for a mysterious phenomenon that has been recognized in recent years in European Incoherent Scatter (EISCAT) UHF incoherent scatter radar (ISR) measurements during many high-power high-frequency (HF) ionospheric pumping experiments. The phenomenon is an apparent increase in electron density observed above the HF reflection altitude, extending up to the observable limits usually in the range 400–650 km, as shown in several publications in recent years. It was shown by Senior et al. (2013) that several examples of these enhanced backscatter could not be explained by increases in electron density. A summary of characteristics of the backscatter enhancements is presented as well as the results of a survey of events. We propose that medium- to large-scale HF-induced field-aligned irregularities (tens to hundreds of metres scale) act to refract the radar signals along the magnetic field, thereby acting as a guide so that the free-space r−2 spreading of the signals no longer applies. The nature of the irregularities and the physical mechanism of their production by powerful HF waves is an exciting topic for future research since, surprisingly, they appear to be preferentially excited by X-mode waves. The explanation proposed here involving HF-induced irregularities may well apply to other ISR observations of the ionosphere in the presence of specific natural irregularities.